Aberrant Promoter Methylation of BRCA1 and RASSF1A in Tumor and Paired Adjacent Normal Tissues from Vietnamese Patients with Breast Cancer - Ha, Ngo Thi; Van, Doan Thi Hong; Ha, Le Thi Thu; Thuan, Ta Bich; Lan, Vo Thi Thuong (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: DNA promoter methylation, a main way of epigenetic regulation, has been studied for detection, prognosis and treatment of breast cancer. In this study, methylation specific polymerase chain reaction (MSP) was used to analyze the promoter methylation of 2 tumor suppressor genes BRCA1 and RASSF1A in tumor and paired adjacent normal tissues of 76 Vietnamese breast cancer patients. We found that tumor and paired adjacent normal tissues were frequently hypermethylated for the two tested genes. The BRCA1 and RASSF1A were highly methylated in tumors (60.5% and 76.3%) and adjacent normal tissues (52.6% and 65.8%), respectively. Further more, there was a high agreement between BRCA1 and RASSF1A methylation in tumor and adjacent tissues (p=0.000050 and p<0.000001). But the differences between methylation in tumor and adjacent tissues were not observed with these genes. On the other hand, there was a significant association between tumor grade and BRCA1 methylation in tumor tissues (p=0.035430), but not with RASSF1A . Beside that, no significant association was observed between methylation status of the two genes and other clinicopathological factors of tumors (age, histological tumor type and metastasis status). Keywords :  Promoter methylation, BRCA1 , RASSF1A , adjacent normal tissues, breast cancer.